BIOCHEMICAL ATTRIBUTES VIS-A-VIS OESTRUS RESPONSE IN CROSS BRED HEIFERS TREATED WITH COMPOUNDED HERBAL DRUGS - S. K. SINGH; D. P. SINGH; RAM NIWAS; HAILESH BHUSHAN SRIVASTAVA; V. K. PASWAN (The Bioscan, 2012)
The effect of compounded herbal drugs (M:A:W and A:W:M) on biochemical parameters of blood viz, serum protein, glucose, total erythrocyte count (TEC) and haemglobin (Hb) concentration, cholesterol and their relationship with oestrus response were observed on eighteen anoestrus cross-bred heifers in three different seasons that is spring, rainy and winter. The results revealed that compounded herbal drugs have significant (p<0.05) impact on all aforesaid biochemical parameters of blood. It was found maximum in M: A: W (T2) treated group under normal range. When analysing the relative importance of biochemical parameters with oestrus response it was also found maximum (72.22 %) in M: A: W (T2) treated group followed by A: W: M (T3) and minimum in control (T1) group. In respect of seasons only blood cholesterol was significantly (p<0.05) affected in treated groups while serum protein, glucose, TEC and Hb were found to be non-significant. The level of blood cholesterol and oestrus response was found best (171.16 mg/100mL and 66.67%, respectively) in spring season. Where as the combined effect of treatments and seasons did not reveal any significant impact on biochemical parameters. But in case of oestrus response it was found best (100%) in spring season treated with M: A: W (T2) compounded herbal drugs.